Shall we ever meet; does it matter: unfreezing the constructs of virtual team effectiveness. (24th April 2020) - Kunte, Monica; Bhattacharya, Sonali; Neelam, Netra
Virtual team has gained significant research attention world over due to its potential to reduce cost and increase productivity. The present study develops a multidimensional virtual team effectiveness scale to measure virtual team members' perceived level of performance. The scale considers virtual team effectiveness as a multidimensional second order construct comprising goal orientation, interdependency, knowledge sharing, empowerment and preparedness. The scale can be used to assess virtual teams' perception towards team performance or effectiveness. Such information would help in formulating strategies on what should be the structure and characteristics of the virtual team and what values can be inculcated on teams before task allotment.